DISTRIBUSI SPASIAL KETAM KENARI (Birgus latro L.) DI PULAU BINONGKO SULAWESI TENGGARA - N. T. Dewi; D. A. Adi; Nasaruddin Nasaruddin (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACTThe research about spatial distribution of Coconut Crab (Birgus latro L.) in Binongko Island Southeast Sulawesi aims to determine the pattern distribution of Coconut Crab (Birgus latro L.). Data survey about estimated of population Coconut Crab (Birgus latro L.) by used CMRR method (Capture Mark Release Recapture). The result showed was the pattern distribution of Coconut Crab (Birgus latro L.) in Binongko Island Southeast Sulawesi is clumped.Keywords : The Coconut Crab (Birgus latro L.), CMRR, and Spatial Distribution